Mesenchymal stem cells alleviate pulmonary fibrosis and gut microbiota dysbiosis in systemic sclerosis - Ni, Biao; Gong, Yufang; Li, Bin; Qiu, Lijie; He, Kang; Guo, Jintao; Fang, Hongkun; Gao, Mingjie; Chen, Min; Wei, Cuie; Sun, Weice; Liu, Bin; et al. (Frontiers in Microbiology, 2025)
IntroductionMesenchymal stem cells (MSCs) have shown the potential to alleviate systemic sclerosis (SSc) tissue fibrosis. However, our knowledge of the effects of MSCs on gut microbiota remains limited.MethodsIn this study, we employed a bleomycin induced SSc model to investigate the effects of MSCs on pulmonary fibrosis and gut microbiota in SSc using transcriptomic, microbial metagenomic, and metabolomic analyses.ResultsOur results indicated that MSCs treatment alleviated lung injury in SSc mice. Transcriptomic analysis suggested that the therapeutic effects of MSCs were primarily associated with fatty acid metabolism, PPAR signaling pathway, and AMPK signaling pathway. Furthermore, MSCs restored the relative abundance of microbial taxa, including Bacteroidota, Actinomycetota, and Akkermansia muciniphila, and improved the gut microbiota dysbiosis induced by SSc. Metabolomic data showed that MSCs modulated the dysregulation of trimethyllysine, cholesteryl sulfate expression, and nicotinate and disturbances in nicotinamide metabolism caused by SSc. Correlation analysis demonstrated significant associations among transcriptomic, microbiomic, and metabolomic datasets.DiscussionCollectively, our findings indicate that MSCs may alleviate SSc pulmonary fibrosis by reshaping the gut microbiota, thereby offering novel scientific insights for the investigation of clinical treatment targets for SSc.